Sustainability Perspective and Awareness Amongst Higher Education in Australia - Issa, Tomayess (2017)
There are positive and negative aspects to the adoption and implementation of sustainability by individuals and businesses. However, if the implementation of sustainability is properly and correctly planned, users will obtain the desired benefits such as financial rewards, brand and reputation enhancement; shareholder satisfaction and human resource efficiency; natural resources conservation; and environmental protection. However, the adoption and implementation of sustainability can have negative consequences in terms of failure and cost. Therefore, to reduce the possibility of these occurring, awareness and training should be made available to individuals and businesses. As discussed in this chapter, the author conducted an online survey with 208 respondents from Australia to examine students’ perspective and awareness toward sustainability. The online survey generated a further three positive and two negative aspects associated with students’ knowledge and understanding of sustainability. Finally, further research will be conducted in future to examine more diverse groups of stakeholders in order to strengthen the research findings.